Pelatihan Nasi Tutug Oncom dengan Konsep Tumpeng sebagai Ide Bisnis UMKM kepada SML UMKM Centre - Yuliantoro, Vincentius Nonot; Evalina, Shelvy; Hapsara, Vriandi; Michelle Setiadi Hartono; Yasinta Kusnin (Gastronary, 2024)
Community Service (CS) focuses on SML UMKM Centre in BSD, South Tangerang, with the theme "Training on Tutug Oncom Rice with the Tumpeng Concept as an UMKM Business Idea." The main objective of this initiative is to provide innovative insights into cooking Tutug Oncom Rice with the Tumpeng concept. This concept supports the development of culinary and business skills, especially in utilizing Oncom as a local Indonesian product. The solution involves conducting training on cooking Tutug Oncom Rice using the Tumpeng concept, along with discussions on business ideas. With the knowledge and skills acquired, it is expected that participants can develop their culinary businesses, enhance the competitiveness of UMKM and create high-quality local products.